Achieving sustainable development goal 9: A study of enterprise resource optimization based on artificial intelligence algorithms - Wang, Zeyu; Deng, Yue; Zhou, Shouan; Wu, Zhongbang (Resources policy, 2023)
Under the rapid economic development trend, exploring the resource optimization strategy of cultural and creative enterprises for sustainable socio-economic development is highly relevant. This study applies the recommendation system to decision-making and resource optimization of entrepreneurial projects for the current situation of complexs entrepreneurial enterprises in the cultural and creative industry (CCI). The neural network algorithm (NNA) is adopted to model project features, user's behavioral and content features. Finally, a recommendation and resource optimization model based on NNA is constructed for CCI-related entrepreneurial projects, and the model is evaluated and analyzed. The results demonstrate that with the increase in the training period, the model's recognition accuracy reaches 81.64%. Besides, the prediction error of the recommender system is minimized when the word vector length is 200, and the number of implied features is 200. Therefore, the entrepreneurial project recommendation and resource optimization model can significantly improve the recognition accuracy and reduce prediction errors, providing experimental references and contributing to the subsequent sustainable development of social economy and entrepreneurial resource optimization. •This paper applies artificial intelligence technology to enterprise resource management to optimize.•This paper combines the concept of resource and the concept of artificial intelligence in theory, and uses rigorous empirical data to verify.•In line with Sustainable Development Goal 9, we have expanded the concept of "resources" from traditional physical resources to different areas.